(untitled) - Mayes, Timothy R. (Mason, OH, 2007)
Start mastering the tool that finance professionals depend upon every day. FINANCIAL ANALYSIS WITH MICROSOFT ® EXCEL covers all the topics you'll see in a corporate finance course: financial statements, budgets, the Market Security Line, pro forma statements, cost of capital, equities, and debt. Plus, it's easy-to-read and full of study tools that will help you succeed in class
Keywords: Microsoft Excel (Computer file),Corporations,Business,Corporations,Electronic spreadsheets,Hệ điều hành máy tính,Bảng số liệu điện tử; Finance,Computer programs,Finance; Computer programs